The Meaning of Profit in Traditional Markets in Frame of Understanding Manunggaling Kawula Lan Gusti - Indah Rakhma Ningtyas, Harfiahani (Journal of Accounting Science, 2024)
General Background: The concept of “Manunggaling Kawula Lan Gusti,” rooted in Javanese culture, embodies the unity between humans and the divine, shaping community dynamics and business practices in traditional markets. Specific Background: This philosophy influences economic and social interactions in Pasuruan’s traditional markets, emphasizing honesty, community empowerment, and spiritual values. Knowledge Gap: While previous studies have addressed “Manunggaling Kawula Lan Gusti” in various contexts, its specific impact on profit perception in traditional markets remains underexplored. Aims: This study investigates how Javanese philosophical principles redefine profit beyond financial metrics, integrating ethical and spiritual dimensions. Results: Ethnographic research reveals that traders prioritize ethical relationships and community well-being, viewing profit as a divine blessing rather than mere monetary gain. Novelty: The study highlights a paradigm shift where success is evaluated through ethical and spiritual contributions, offering a sustainable business model that transcends financial success. Implications: This research suggests integrating cultural philosophies like “Manunggaling Kawula Lan Gusti” into modern business practices can enhance ethical standards, community relations, and spiritual fulfilment, encouraging businesses globally to adopt more holistic success measures.